Spatio-temporal reconstruction of emergent flash synchronization in firefly swarms via stereoscopic 360-degree cameras. Issue 170 (30th September 2020) - Sarfati, Raphaël; Hayes, Julie C.; Sarfati, Élie; Peleg, Orit
Abstract : During mating season, males of synchronous firefly species flash in unison within swarms of thousands of individuals. These strongly correlated collective displays have inspired numerous mathematical models to explain how global synchronous patterns emerge from local interactions. Yet, experimental data to validate these models remain sparse. To address this gap, we develop a method for three-dimensional tracking of firefly flashes, using a stereoscopic set-up of 360-degree cameras. We apply this method to record flashing displays of the North American synchronous species Photinus carolinus in its natural habitat as well as within controlled environments, and obtain the three-dimensional reconstruction of flash occurrences in the swarm. Our results show that even a small number of interacting males synchronize their flashes; however, periodic flash bursts only occur in groups larger than 15 males. Moreover, flash occurrences are correlated over several metres, indicating long-range interactions. While this suggests emergent collective behaviour and cooperation, we identify distinct individual trajectories that hint at additional competitive mechanisms. These reveal possible behavioural differentiation with early flashers being more mobile and flashing longer than late followers. Our experimental technique is inexpensive and easily implemented. It is extensible to tracking light communication in various firefly species and flight trajectories in other insect swarms.